A Synthesis of Functionalized 2-Indolizin-3-yl-1,3-benzothiazoles from 1-(1,3-Benzothiazol-2-ylmethyl)pyridinium Iodide and Acetylenic Esters - Yavari, Issa; Ghafouri, Kiyana; Naeimabadi, Maryam; Halvagar, Mohammad Reza (Synlett, 2018)
Functionalized 2-indolizin-3-yl-1,3-benzothiazoles were obtained in moderate yields from the reaction between 1-(1,3-benzothiazol-2-ylmethyl)pyridinium iodide and acetylenic esters in acetonitrile. When isoquinoline was used under similar conditions, dialkyl 3-(1,3-benzothiazol-2-yl)pyrrolo[2,1-a]isoquinoline-1,2-dicarboxylates were obtained. The structures of these products have been confirmed by X-ray diffractometry.
Keywords: indolizinylbenzothiazoles; alkynoate esters; ylide; benzothiazolylpyrroloisoquinolines